Analisis Sosiologis Peran dan Interaksi Tenaga Kerja terhadap Produktivitas di Industri Farmasi - Tara Shinta Yuliani; Didin Syarifuddin (El-Mujtama: Jurnal Pengabdian Masyarakat, 2026)
This research focuses on understanding how workforce roles and interactions influence productivity in the pharmaceutical industry, using a case study at PT Novell Pharmaceutical Laboratories Gunung Putri, Bogor. The researchers believe that productivity is not solely determined by technical and procedural aspects but is also shaped by the social dynamics of the workplace. This study employed a qualitative approach, combining literature review, field observations, and in-depth interviews with several employees at PT Novell. This method was used to understand daily work practices in a production environment subject to strict regulations. The findings indicate that a clear division of roles plays a crucial role in maintaining smooth work coordination and reducing the potential for operational errors. Furthermore, the quality of social interactions among workers tends to influence the effectiveness of collaboration, particularly in processes that demand precision and consistency. These findings demonstrate that productivity in the pharmaceutical industry needs to be understood as a result of a combination of technical and social aspects, making a sociological perspective relevant in human resource management.